2005
DOI: 10.1099/mic.0.28221-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes associated with mutacin I production in Streptococcus mutans using random insertional mutagenesis

Abstract: Streptococcus mutans is a major pathogen implicated in dental caries. Its virulence is enhanced by its ability to produce bacteriocins, called mutacins, which inhibit the growth of other Gram-positive bacteria. The goal of this study is to use a random insertional mutagenesis approach to search for genes that are associated with mutacin I production in the virulent strain UA140. A random insertional mutagenesis library consisting of 11 000 clones was constructed and screened for a mutacin-defective phenotype. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 62 publications
0
30
0
1
Order By: Relevance
“…A role for VicK in mutacin I production was also demonstrated by Tsang et al using a random insertional mutagenesis approach in the virulent strain UA140 (53). In that study, disruption of the VicRK was shown to abolish mutacin I production.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…A role for VicK in mutacin I production was also demonstrated by Tsang et al using a random insertional mutagenesis approach in the virulent strain UA140 (53). In that study, disruption of the VicRK was shown to abolish mutacin I production.…”
Section: Resultsmentioning
confidence: 71%
“…In that study, disruption of the VicRK was shown to abolish mutacin I production. It was later discovered that while both VicK and a stress response regulator called HrcA were needed to produce mutacin I, VicK's influence on mutacin I synthesis was exerted by controlling transcription of a putative stressresponsive regulator designated irvA (inducible repressor of virulence A) for its role as a repressor for mutacin I synthesis in S. mutans (53,54). In our microarray experiments, we observed that loss of VicK reduced the transcription of hrcA by Ͼ2.5-fold (see Table S1 in the supplemental material).…”
Section: Resultsmentioning
confidence: 99%
“…Some recent molecular and genetic studies have revealed that bacteriocin production is a well-regulated event which is affected by both environmental conditions, such as cell density, nutritional availability, and pH, and genetic factors (100,101,136,162,203). These regulatory systems ensure that bacteriocins are produced at the right time and place so that they can be effectively used for "war and peace" activities within an oral microbial community.…”
Section: Bacteriocins and Their Role In Interspecies Interaction Withmentioning
confidence: 99%
“…A majority of the mutacins characterized to date belong to lantibiotics, such as the mutacins I, II, III, K8, B-Ny266, Smb, and 1140 (30)(31)(32)(33)(34)(35)(36)(37). Based on the primary amino acid sequences, mutacins belonging to lantibiotics are further subdivided into two subclasses: AI and AII (38)(39)(40).…”
mentioning
confidence: 99%